Prevalence of Nutraceutical Use in Younger Population of North India and the Association Between Gender and Community in Its Usage – Cross-Sectional Study - SARAN, Divya; Bansal, Alka; Agrawal, Ashish; Sharma, Lokendra; Jain, Smita; Jakhar, Punam (Scripta Medica, 2023)
Background/Aim: Nutraceuticals or dietary supplements have been recognised as a fundamental part of the holistic approach to achieve complete wellness and health. Their usage is continuously increasing due to lifestyle and sport-style requirements. The present study was designed to estimate the use of nutraceuticals in the younger population and find the association between gender and community in their usage.Methods: An observational cross-sectional survey was carried out on the younger population of North India between the ages of 15 and 30 years over a period of two weeks in October 2022, following ethical approval. The data regarding the demographic profile and nutraceutical use among participants was collected per predesigned and pre-validated questionnaire. The collected data was analysed to determine the outcomes.Results: The study included 575 participants, with 272 males and 303 females. Out of them, 321 were from the urban background. It was found in the study that a total of 275 (47.82 %) study subjects were using nutraceuticals, with 163 (59.27 %) and 112 (40.73 %) from the urban and rural dwellings, respectively. Among the users, 122 (44.36 %) were men and 153 (55.64 %) were women. Thus, overall, 153 (50.49 %) of females and 122 (44.85 %) of males in survey were consuming dietary supplements. The study further added that 189 (68.72 %) users believed that nutraceuticals improved their health, two-thirds of participants were using nutraceuticals for lifestyle reasons and 239 (86.90 %) of consumers were using single nutraceuticals. There was no association between gender and community in nutraceuticals usage (Chi-square test, p > 0.05).Conclusion: Almost half of the younger population was using nutraceuticals and there was no association between gender and community while using them.